2018
DOI: 10.3390/dj6010002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Oral Hygiene Instructions Given in Computer-Assisted Format versus a Self-Care Instructor

Abstract: Background: This randomized, single-blinded, controlled study compares the effectiveness of two modes of delivering the same set of oral hygiene instructions: those loaded on a computer-assisted teaching format versus those given personally by a self-care instructor. Methods: 60 participants with mild to moderate periodontitis were randomized to either the computer-teaching format or the self-care instructor. Plaque score and bleeding indices were assessed at baseline and at 4 week re-evaluation to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…42 Therefore, studies on oral hygiene techniques indicate that appropriate techniques in use for a long time (modified Bass technique, modified Stillmann technique, Charter technique) are significant in the prevention of periodontal diseases. 43 Our study indicated that almost all students who brush their tongue brush their teeth. However, only 40% of students who brush their teeth brush their tongue.…”
Section: Variablesmentioning
confidence: 68%
“…42 Therefore, studies on oral hygiene techniques indicate that appropriate techniques in use for a long time (modified Bass technique, modified Stillmann technique, Charter technique) are significant in the prevention of periodontal diseases. 43 Our study indicated that almost all students who brush their tongue brush their teeth. However, only 40% of students who brush their teeth brush their tongue.…”
Section: Variablesmentioning
confidence: 68%
“…Accumulating evidence has revealed that DA is associated with pain perception and patient satisfaction related to dental procedures . Different surgical procedures may cause anxiety for different reasons . Patients may not be able to cooperate with dentists when they experience anxiety during dental treatment, which may increase the amount of time needed and the level of difficulty in performing procedures, thereby causing unsatisfactory treatment results …”
Section: Introductionmentioning
confidence: 99%
“…1 Approximately two in three patients undergoing dental implant surgeries experience moderate or high preoperative DA. 2 Accumulating evidence has revealed that DA is associated with pain perception and patient satisfaction related to dental procedures. [3][4][5][6] Different surgical procedures may cause anxiety for different reasons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations